Perbandingan Idiom yang Berunsur Bagian Tubuh Manusia Pada Bahasa Vietnam dan Indonesia (Comparison of Idioms with Human Body Parts in Vietnamese and Indonesian) - Ho Ngoc Hieu; Ribut Wahyu Eriyanti; Daroe Iswatiningsih (Jurusan Tadris Bahasa Indonesia, 2022)
This study aims to describe (1) the similarities and differences in the forms of idioms containing BTM elements in BV and BI and (2) the similarities and differences in the meanings of idioms containing BTM elements in BV and BI. This study uses a qualitative descriptive approach with a contrastive analysis method. The results of this study indicate that (1) in terms of form there are, (a) idioms with the same form and meaning, (b) idioms with the same form but different meanings, and (c) idioms with different forms, but the same meaning in BV and BI ; (2) in terms of meaning, there are similarities and differences (a) full meaning and partial meaning, (b) context meaning, and (c) value meaning. The results of this study can be used as teaching materials for BIPA learning, especially for students from Vietnam.Penelitian ini bertujuan mendeskripsikan (1) persamaan dan perbedaan bentuk idiom yang berunsur BTM pada BV dan BI dan (2) persamaan dan perbedaan makna idiom yang berunsur BTM pada BV dan BI. Penelitian ini menggunakan pendekatan deskriptif kulaitatif dengan metode analisis kontrastif. Hasil penelitian ini menunjukkan bahwa (1) dari segi bentuknya terdapat, (a) idiom yang sama bentuk dan makna, (b) idiom yang sama bentuk tetapi maknanya berbeda, dan (c) idiom yang beda bentuk, tetapi maknanya sama dalam BV dan BI; (2) dari segi maknanya terdapat persamaan dan perbedaan (a) makna penuh dan makna sebagian, (b) makna konteks, dan (c) makna nilai. Hasil penelitian ini dapat dimanfaatkan sebagai bahan ajar pembelajaran BIPA, khususnya bagi pemelajar dari Vietnam.